Prevalence of long COVID-19 among healthcare workers: a systematic review and meta-analysis protocol - Shirley Sze; Katherine Woolf; Manish Pareek; Carolyn Tarrant; Daniel Pan; Christopher A Martin; Mayuri Gogoi; Amani Al-Oraibi; Joshua Nazareth; Jatin Sridhar Naidu; Aasiya Chaka; Laura B Nellums (BMJ Open, 2022)
Introduction A proportion of those who survive the acute phase of COVID-19 experience prolonged symptoms, commonly known as long COVID-19. Given that healthcare workers (HCWs) face an elevated risk of acute COVID-19 compared with the general population, the global burden of long COVID-19 in HCWs is likely to be large; however, there is limited understanding of the prevalence of long COVID-19 in HCWs, or its symptoms and their clustering. This review will aim to estimate the pooled prevalence and the symptoms of long COVID-19 among HCWs infected with SARS-CoV-2 globally, and investigate differences by country, age, sex, ethnicity, vaccination status and occupation.Methods and analysis A systematic review and meta-analysis will be conducted. Medline (via Ovid), CINAHL (via EBSCO), Embase (via Ovid), PsycINFO (via EBSCO), OpenGrey (grey literature) and medRxiv (preprint server) will be searched from the 31 December 2019 onward. All research studies and preprint articles reporting any primary data on the prevalence and/or the symptoms of long COVID-19 among adult HCWs will be included. Methodological quality will be assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data. Outcomes are anticipated to be the prevalence of long COVID-19 among HCWs around the world and trajectory of symptoms. Data synthesis will include random-effect meta-analysis for studies reporting prevalence data of long COVID-19 following SARS-CoV-2 infection among HCWs. The results will be presented with a 95% CI as an estimated effect across studies. Heterogeneity will be assessed using I² statistic. Where meta-analysis is inappropriate, a narrative synthesis of the evidence will be conducted.Ethics and dissemination Ethical approval is not needed as data will be obtained from published articles. We will publish our findings in a peer-reviewed journal and disseminate the results of our review at conferences.PROSPERO registration number CRD42022312781.